Egyptian Rousette IFN-ω Subtypes Elicit Distinct Antiviral Effects and Transcriptional Responses in Conspecific Cells - Pavlovich, Stephanie S.; Darling, Tamarand; Hume, Adam J.; Davey, Robert A.; Feng, Feng; Mühlberger, Elke; Kepler, Thomas B. (Frontiers in Immunology, 2020)
Bats host a number of viruses that cause severe disease in humans without experiencing overt symptoms of disease themselves. While the mechanisms underlying this ability to avoid sickness are not known, deep sequencing studies of bat genomes have uncovered genetic adaptations that may have functional importance in the antiviral response of these animals. Egyptian rousette bats (Rousettus aegyptiacus) are the natural reservoir hosts of Marburg virus (MARV). In contrast to humans, these bats do not become sick when infected with MARV. A striking difference to the human genome is that Egyptian rousettes have an expanded repertoire of interferon-omega (IFN-ω) genes. To probe the biological implications of this expansion, we synthesized IFN-ω4 and IFN-ω9 proteins and tested their antiviral activity in Egyptian rousette cells. Both IFN-ω4 and IFN-ω9 showed antiviral activity against RNA viruses, including MARV, with IFN-ω9 being more efficient than IFN-ω4. Using RNA-Seq, we examined the transcriptional response induced by each protein. Although the sets of genes induced by the two IFNs were largely overlapping, IFN-ω9 induced a more rapid and intense response than did IFN-ω4. About 18% of genes induced by IFN-ω treatment are not found in the Interferome database, indicating that they may be uniquely IFN-responsive in this bat.